Visualization of Dynamic Mitochondrial Calcium Fluxes in Isolated Cardiomyocytes - Krstic, Anna Maria; Power, Amelia Sally; Ward, Marie-Louise (Frontiers in Physiology, 2022)
Background Cardiomyocyte contraction requires a constant supply of ATP, which varies depending on work rate. Maintaining ATP supply is particularly important during excitation-contraction coupling, where cytosolic Ca2+ fluxes drive repeated cycles of contraction and relaxation. Ca2+ is a key regulators of ATP production, and its uptake into the mitochondrial matrix occurs via the mitochondrial calcium uniporter. Fluorescent indicators are commonly used for detecting cytosolic Ca2+ changes. However, visualizing mitochondrial Ca2+ fluxes using similar methods is more difficult, as the fluorophore must be permeable to both the sarcolemma and the inner mitochondrial membrane. Our aim was therefore to optimize a method using the fluorescent Ca2+ indicator Rhod-2AM to visualize beat-to-beat mitochondrial calcium fluxes in rat cardiomyocytes. Methods Healthy, adult male Wistar rat hearts were isolated and enzymatically digested to yield rod-shaped, quiescent ventricular cardiomyocytes. The fluorescent Ca2+ indicator Rhod-2AM was reduced to di-hydroRhod-2AM and confocal microscopy was used to validate mitochondrial compartmentalization. Cardiomyocytes were subjected to various pharmacological interventions, including caffeine and β-adrenergic stimulation. Upon confirmation of mitochondrial Rhod-2 localization, loaded myocytes were then super-fused with 1.5 mM Ca2+ Tyrodes containing 1 µM isoproterenol and 150 µM spermine. Myocytes were externally stimulated at 0.1, 0.5 and 1 Hz and whole cell recordings of both intracellular ([Ca2+]i) and mitochondrial calcium ([Ca2+]mito) transients were made. Results Myocytes loaded with di-hydroRhod-2AM revealed a distinct mitochondrial pattern when visualised by confocal microscopy. Application of 20 mM caffeine revealed no change in fluorescence, confirming no sarcoplasmic reticulum compartmentalization. Myocytes loaded with di-hydroRhod-2AM also showed a large increase in fluorescence within the mitochondria in response to β-adrenergic stimulation (P<0.05). Beat-to-beat mitochondrial Ca2+ transients were smaller in amplitude and had a slower time to peak and maximum rate of rise relative to cytosolic calcium transients at all stimulation frequencies (P<0.001). Conclusions Myocytes loaded with di-hydroRhod-2AM revealed mitochondrial specific compartmentalization. Mitochondrial Ca2+ transients recorded from di-hydroRhod-2AM loaded myocytes were distinct in comparison to the large and rapid Rhod-2AM cytosolic transients, indicating different kinetics between [Ca2+]cyto and [Ca2+]mito transients. Overall, our results showed that di-hydroRhod-2AM loading is a quick and suitable method for measuring beat-to-beat [Ca2+]mito transients in intact myocytes.